Bow Hunter's syndrome with clicking sounds: A rare etiology of transient loss of consciousness with tonic–clonic seizure - Wang, Lijuan; Dong, Yanan; Chen, Hongxiu; Bai, Jing; Zhu, Mingqin; Xing, Yingqi (Frontiers in Neurology, 2023)
We present the case of a young male patient experiencing a transient loss of consciousness and manifesting a seizure when he tilted his head backward. Transcranial Doppler ultrasound (TCD) and carotid artery ultrasound (CAU) examination were normal when the patient's neck was in the neutral position. However, the CAU revealed vertebral artery (VA) transient occlusion during neck rotation or backward movement. Electroencephalogram (EEG) monitoring was performed with multiple neck rotation–induced tests. The patient developed dizziness, which was the same as the prodromal symptoms of the first seizure, and the EEG showed a large number of spinal slow waves and sharp slow waves in the frontal-to-frontal midline area, with an occasional generalization trend. CT angiography revealed occipitalization of the atlas and the lack of contrast agent filling in the local area of the VA when the patient's head was turned contralaterally. Thus, the patient was diagnosed with Bow Hunter's syndrome (BHS) and treated conservatively with neck immobilization. No recurrence occurred at 3 and 6 months of follow-up. Therefore, this case alerts neurologists to suspect BHS on observing seizure manifestations during neck rotation, and CAU may be a recommended dynamic screening method for BHS. This report is accompanied by a discussion of the phenomenon and diagnosis in the context of the existing literature.